Advances in Extra-corporeal Perfusion Therapies - Firstenberg, Michael S. (IntechOpen, 2019)
Extracorporeal membrane oxygenation (ECMO) has evolved into an exciting and valuable tool to assist in the management of patients experiencing cardiogenic shock, severe acute respiratory failure, or often a combination of both. While outcomes remain less than ideal, they continue to improve with team experience, better patient selection, and a growing understanding of the nuances of managing patients who require mechanical circulatory support. Patients requiring ECMO are often extremely sick and have complex problems - initiating therapy before the development of end-organ damage is critical. Without doubt, teamwork, guidelines, and protocols are cornerstone concepts for clinical and program success - all topics that are emphasized in this text. The goals of this text are to further outline topics that help address some of the key challenges providers face when considering and applying extracorporeal support therapies to the evolving spectrum of acutely ill patients.